2019
DOI: 10.3390/molecules24020273
|View full text |Cite
|
Sign up to set email alerts
|

Castanopsis lamontii Water Extract Shows Potential in Suppressing Pathogens, Lipopolysaccharide-Induced Inflammation and Oxidative Stress-Induced Cell Injury

Abstract: Castanopsis lamontii is traditionally used to prevent inflammatory diseases such as periodontitis and pharyngitis by residents in southwest China. However, little scientific evidence has been found to support this. In this research, the antibacterial activities of Castanopsis lamontii water extract (CLE) were assessed using the micro-dilution method. The anti-inflammatory and antioxidant activities of CLE were investigated in RAW264.7 cells. Key bioactive compounds in CLE were also explored. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Moreover, the P. gingivalis inhibitory effect of the tested Sri Lankan TBQ extract was higher than that of many other herbal extracts reported to have antiperiodontopathic effects. Even the MICs of the water extract of Polygonum tinctorium Lour (MIC:1.74 mg/ml), methanol extract of Terminalia laxiflora (MIC:0.25 mg/ml), methanol extracts of Ambrosia maritima (MIC:0.5 mg/ml), seeds of Argemone mexicana (MIC: 0.5 mg/ml), wood and bark of Terminalia brownii (MIC: 0.5 mg/ml), bark of Combretum hartmannianum (MIC: 0.5 mg/ml), bark of Acacia tortilis (MIC:0.5 mg/ml) and the ethanol extract of Piper marginatum Jacq (MIC: 1 mg/ml), ethanol extract of Ilex guayusa Loes (MIC: 1 mg/ml) methanol extract of Phytolacca americana (MIC: 600 μg/ml), water extract of Camellia sinensis/ green tea (MIC: 12.5 mg/ml), ethanolic extract of Allium sativum/ garlic (MIC: 62.5 mg/ml), ethanolic extract of Mammea americana (MIC: 500 μg/ml), and the water extract of Castanopsis lamontii (MIC: 625 μg/ml) were higher than the MBC of the TBQ extract against P. gingivalis [ 34 , 45 51 ]. According to Kohlie et al, ethanol extract of the husk of Coccus nucifera also has a lower P. gingivalis inhibitory effect (MBC:1562.5 μg/ml) compared to that of the tested TBQ extract [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the P. gingivalis inhibitory effect of the tested Sri Lankan TBQ extract was higher than that of many other herbal extracts reported to have antiperiodontopathic effects. Even the MICs of the water extract of Polygonum tinctorium Lour (MIC:1.74 mg/ml), methanol extract of Terminalia laxiflora (MIC:0.25 mg/ml), methanol extracts of Ambrosia maritima (MIC:0.5 mg/ml), seeds of Argemone mexicana (MIC: 0.5 mg/ml), wood and bark of Terminalia brownii (MIC: 0.5 mg/ml), bark of Combretum hartmannianum (MIC: 0.5 mg/ml), bark of Acacia tortilis (MIC:0.5 mg/ml) and the ethanol extract of Piper marginatum Jacq (MIC: 1 mg/ml), ethanol extract of Ilex guayusa Loes (MIC: 1 mg/ml) methanol extract of Phytolacca americana (MIC: 600 μg/ml), water extract of Camellia sinensis/ green tea (MIC: 12.5 mg/ml), ethanolic extract of Allium sativum/ garlic (MIC: 62.5 mg/ml), ethanolic extract of Mammea americana (MIC: 500 μg/ml), and the water extract of Castanopsis lamontii (MIC: 625 μg/ml) were higher than the MBC of the TBQ extract against P. gingivalis [ 34 , 45 51 ]. According to Kohlie et al, ethanol extract of the husk of Coccus nucifera also has a lower P. gingivalis inhibitory effect (MBC:1562.5 μg/ml) compared to that of the tested TBQ extract [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asahi et al [32] demonstrated that EGCG (500 μg/mL is liklely based on a mechanism distinct from that responsible for its bactericidal activity at high concentrations. Gao et al [20] studied the buds of Castanopsis lamontii Hance water extract (CLE) rich in epicatechin and procyanidin B2, confirming inhibition of P. gingivalis growth by flavan-3-ols or proanthocyanidins only at high concentrations.…”
Section: Pgingivalis Prevotella Speciesmentioning
confidence: 99%
“…Inhibition of the adherence of P. gingivalis onto epithelial cells was much more effective when EGCg was preincubated with bacteria than with epithelial cells. ( Sakanaka et al 1996) [46] [20]. However, it is supposed that the most important virulence factors are cysteine proteases-the arginine-specific (RgpA and RgpB) and lysine-specific (Kgp) gingipains, which are attributed to 85% of the total proteolytic activity of P. gingivalis [47].…”
Section: Pgingivalis Prevotella Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants fight against toxicity in different ways including physical responses (such as exclusion the toxic elements through cell wall or their isolation in vacuole) and biochemical reactions (like scavenging reactive oxygen species (ROS) by the activities of antioxidant enzymes and a raise in secondary metabolites contents). But excessive amounts of toxic elements defeat the defense system of plants and reduce germination, growth, and development, and eventually cause death [4,5,6].…”
Section: Introductionmentioning
confidence: 99%